KAJIAN KETARJIHAN BAGI PIMPINAN DAN MUBALIGH/ MUBALIGHAT RANTING MUHAMMADIYAH/’AISYIYAH PENDOWOHARJO TIMUR - Abd. Madjid; Siti Bahiroh (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This community service activity focuses on providing information on Muhammadiyah tarjih fatwas for leaders, Muhammadiyah preachers and Muballighoh Aisyiyah East Pendowoharjo branch. The method used is through counseling and training on Muhammadiyah tarjih fatwas with a focus on studies in the fields of fasting, zakat and sacrificial worship. The results of outreach and training activities show that before this activity was held, the average knowledge and skills of leaders, missionaries and preachers in terms of knowledge was 60%. However, after implementation, there was a significant increase, as seen from the post-test results which showed that the average participant's knowledge and abilities increased to 90.5%. This series of activities has proven to be eflective in increasing the knowledge, understanding and skills of Muhammadiyah/Aisyiyah leaders, preachers and muballighoh so that Muhammadiyah tarjih fatwas reach the citizens and people correctly.